Electricity generation and dibenzothiophene biodegradation using a novel electroactive bacterium Lysinibacillus macroides AP in microbial fuel cells - Zihan Huang; Lei Zhang; Ting Cai; Ruijun Liu; Xiaoyan Qi; Xia Wang (Engineering Microbiology)
Polycyclic aromatic sulfur heterocycles, such as dibenzothiophene (DBT), and their alkylated derivatives are recognized as persistent and toxic contaminants that pose major risks to the environment and human health. Here, a novel electroactive gram-positive bacterium, Lysinibacillus macroides AP, was isolated and identified from a microbial fuel cell (MFC) powered by aromatic compounds. An electricity generation performance with a maximum discharge voltage of 424.59 mV and a power density of 420.95 mW m⁻2 was obtained using L. macroides AP in an MFC fueled with sodium formate. An analysis of the extracellular electron transfer (EET) mechanism indicated that the endogenous redox mediators produced by L. macroides AP were not detected, but exogenous redox mediators such as thionine acetate and anthraquinone-2, 6-disulfonate could temporarily enhance EET. The characterization of biofilm morphology revealed a dense network of microbial nanowires on the cell surface of L. macroides AP; the abundance of these nanowires was positively correlated with the discharge efficiency of the MFC, suggesting that the nanowires generated by L. macroides AP cells were likely to promote EET. Additionally, effective bioelectricity generation and simultaneous DBT degradation were successfully achieved using L. macroides AP in MFCs, with a power density of 385.20 mW m⁻2 and 88.72 % DBT removal. This is the first report on a novel ecological role of L. macroides AP as a gram-positive electroactive bacterium, emphasizing its potential applications in environmental remediation and energy recovery.